Piezoelectric film laminate and method for manufacturing same

By forming a ScAlN film in contact with an insulating amorphous film within a piezoelectric film laminate, the crystallinity and piezoelectricity of the ScAlN film are improved, addressing the issue of reduced crystallinity due to electrode or substrate influences.

JP7647466B2Active Publication Date: 2025-03-18DENSO CORP +2
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021150235
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-15
Publication Date
2025-03-18
Estimated Expiration
2041-09-15

AI Technical Summary

Technical Problem

The crystallinity of ScAlN films in piezoelectric film laminates is reduced when formed in contact with electrodes or under substrates with residual stress, leading to decreased piezoelectricity.

Method used

A piezoelectric film laminate is created with a metal film, an insulating amorphous film, and a ScAlN film, where the ScAlN film is formed in contact with the surface of the amorphous film, allowing self-orientation and higher crystallinity without influence from the underlying substrate.

Benefits of technology

This approach results in a ScAlN film with higher crystallinity and improved piezoelectric properties, enhancing the performance of piezoelectric film laminates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647466000001
    Figure 0007647466000001
  • Figure 0007647466000002
    Figure 0007647466000002
  • Figure 0007647466000003
    Figure 0007647466000003
Patent Text Reader

Abstract

To provide a piezoelectric film laminate having a ScAlN film with high crystallinity.SOLUTION: A piezoelectric film laminate 10 includes a metal film 11, an insulative amorphous film 12, and a ScAlN film 13. The metal film 11 is made of a metal material. The amorphous film 12 is formed on the metal film 11. The ScAlN film 13 is formed on the amorphous film 12 in contact with a surface of the amorphous film 12. As a result, it is possible to form the ScAlN film 13 having high crystallinity as compared with a case where the ScAlN film is formed in contact with a surface of an underlayer having a crystal structure.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a piezoelectric film laminate and a method for manufacturing the same. [Background technology]

[0002] Patent Document 1 discloses a piezoelectric film laminate including a lower electrode and a ScAlN film disposed on the lower electrode. The ScAlN film is a piezoelectric film. The lower electrode is an electrode disposed below the ScAlN film. This piezoelectric film laminate constitutes a part of various devices. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 5190841 Summary of the Invention [Problem to be solved by the invention]

[0004] In manufacturing the piezoelectric film laminate having the above structure, when the ScAlN film is formed in contact with the surface of the electrode, the crystallinity of the resulting ScAlN film decreases depending on the material constituting the electrode or the magnitude of the residual stress in the ScAlN film. When the crystallinity of the ScAlN film decreases, the piezoelectricity of the ScAlN film decreases.

[0005] An object of the present invention is to provide a piezoelectric film laminate including a highly crystalline ScAlN film. Another object of the present invention is to provide a method for manufacturing a piezoelectric film laminate including a highly crystalline ScAlN film. [Means for solving the problem]

[0006] In order to achieve the above object, according to the invention described in claim 1, a piezoelectric film laminate is A metal film (11); an insulating amorphous film (12) disposed on the metal film; a ScAlN film (13) disposed on the amorphous film and in contact with the surface of the amorphous film; The thickness of the amorphous film is 1.0 nm or more, and is 1 / 10 or less of the thickness of the ScAlN film. .

[0007] According to this, the ScAlN film is formed in contact with the surface of the amorphous film. Therefore, the ScAlN can be self-oriented without being affected by the crystal structure of the base. Therefore, a ScAlN film with high crystallinity can be formed compared to when the ScAlN film is formed in contact with the surface of a base having a crystalline structure. Therefore, a piezoelectric film laminate including a ScAlN film with high crystallinity can be provided.

[0008] In addition, claims 5 According to the invention described in the above, the piezoelectric film laminate is A conductive amorphous film (14, 16); and an ScAlN film (13) disposed on the amorphous film and in contact with the surface of the amorphous film.

[0009] According to this, the ScAlN film is formed in contact with the surface of the amorphous film. Therefore, the ScAlN can be self-oriented without being affected by the crystal structure of the base. Therefore, a ScAlN film with high crystallinity can be formed compared to when the ScAlN film is formed in contact with the surface of a base having a crystalline structure. Therefore, a piezoelectric film laminate including a ScAlN film with high crystallinity can be provided.

[0010] In addition, claims 10 According to the invention described in the above, a method for producing a piezoelectric film laminate includes the steps of: forming a metal film (11); forming an insulating amorphous film (12) on the metal film; forming an ScAlN film (13) on the amorphous film so as to be in contact with a surface of the amorphous film; In forming an amorphous film, the surface layer of the metal film is oxidized or nitrided. The film thickness is 1.0 nm or more and 1 / 10 or less of the film thickness of the ScAlN film. An amorphous film is formed.

[0011] This makes it possible to manufacture the piezoelectric film laminate according to claim 1. This allows the ScAlN film to be formed in contact with the surface of the amorphous film. Therefore, the ScAlN can be self-oriented without being affected by the crystal structure of the base. This makes it possible to form an ScAlN film with higher crystallinity than when the ScAlN film is formed in contact with the surface of a base having a crystalline structure. Therefore, it is possible to provide a method for manufacturing a piezoelectric film laminate including a ScAlN film with higher crystallinity.

[0012] In addition, claims 17 According to the invention described in the above, a method for producing a piezoelectric film laminate includes the steps of: forming a conductive amorphous film (16); forming an ScAlN film (13) on the amorphous film so as to be in contact with a surface of the amorphous film; In forming the amorphous film, the metal film (15) is subjected to ion implantation or plasma treatment to form the amorphous film.

[0013] According to this, claim 5 It is possible to manufacture the piezoelectric film laminate described in the above. According to this, an ScAlN film is formed in contact with the surface of an amorphous film. Therefore, ScAlN can be self-oriented without being affected by the crystal structure of the base. Therefore, an ScAlN film with high crystallinity can be formed compared to when the ScAlN film is formed in contact with the surface of a base having a crystal structure. Therefore, it is possible to provide a manufacturing method for a piezoelectric film laminate including a ScAlN film with high crystallinity.

[0014] Note that the reference symbols in parentheses attached to each component indicate an example of the correspondence between the component and specific components described in the embodiments described below. [Brief description of the drawings]

[0015] [Figure 1] 1 is a cross-sectional view of a piezoelectric film laminate in a first embodiment. [Diagram 2]4 is a flowchart showing a method for manufacturing a piezoelectric film laminate in the first embodiment. [Diagram 3] 3 is a graph showing the relationship between the exposure time in the air in the amorphous film formation step in FIG. 2 and the film thickness of the amorphous film formed by exposure in the air. [Figure 4] 3 is a graph showing the relationship between the exposure time in the air in the amorphous film formation step in FIG. 2 and the crystallinity of the ScAlN film. [Diagram 5] FIG. 11 is a cross-sectional view of a piezoelectric film laminate in a third embodiment. [Figure 6] FIG. 13 is a cross-sectional view of a piezoelectric film laminate in a fourth embodiment. [Figure 7] 13 is a flowchart showing a method for manufacturing a piezoelectric film laminate in a fourth embodiment. [Figure 8] FIG. 13 is a cross-sectional view of a microphone in a fifth embodiment. [Figure 9] FIG. 13 is a perspective view of a BAW resonator according to a sixth embodiment. [Figure 10] FIG. 13 is a perspective view of a SAW device in a seventh embodiment. [Figure 11] FIG. 13 is a cross-sectional view of a MEMS resonator according to an eighth embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, embodiments of the present invention will be described with reference to the drawings. In the following embodiments, parts that are the same or equivalent to each other will be denoted by the same reference numerals.

[0017] (First embodiment) As shown in FIG. 1, a piezoelectric film laminate 10 of this embodiment includes a substrate 1, a metal film 11, an insulating amorphous film 12, and a ScAlN film 13.

[0018] The base material 1 is made of a semiconductor material, an insulating material, etc. As the base material 1, for example, a Si substrate is used.

[0019] The metal film 11 is a film made of a metal material. The metal film 11 is used as a lower electrode in a device. The metal film 11 is disposed on a substrate 1. The metal film 11 is in contact with the surface of the substrate 1. Note that one or more other films may be disposed between the metal film 11 and the substrate 1. That is, the metal film 11 may be in contact with the surface of another film on the substrate 1.

[0020] The amorphous film 12 is disposed on the metal film 11. The amorphous film 12 is in contact with the surface of the metal film 11. The amorphous film 12 is used as a base for the ScAlN film 13.

[0021] The amorphous film 12 is a film made of an insulating amorphous material. In this specification, the term "insulating" refers to a film having an electrical resistivity (i.e., volume resistivity) of 10 4 This means that the resistivity is Ω·m or more. Amorphous refers to a state of a substance that does not have a crystal structure, and is also called non-crystalline. Whether the material constituting the amorphous film 12 is amorphous can be confirmed by performing electron beam diffraction measurement on the amorphous film 12. When the measurement result is a halo pattern, the material constituting the amorphous film 12 is amorphous. Examples of materials constituting the amorphous film 12 include materials containing metal oxides, metal nitrides, etc.

[0022] As will be seen from the experimental results described later, when the thickness of the amorphous film 12 is in the range of less than 1.0 nm, the crystallinity of the ScAlN film 13 increases as the thickness of the amorphous film 12 increases. When the thickness of the amorphous film 12 is in the range of 1.0 nm or more, the level of crystallinity of the ScAlN film 13 is approximately the same regardless of the thickness of the amorphous film 12, and the crystallinity of the ScAlN film 13 is higher than when the thickness of the amorphous film 12 is in the range of less than 1.0 nm. For this reason, it is preferable that the thickness of the amorphous film 12 is 1.0 nm or more.

[0023] However, as the thickness of the amorphous film 12 increases, the overall piezoelectricity of the composite film including the ScAlN film 13 and the amorphous film 12 is impaired. For this reason, the thickness of the amorphous film 12 is set so as not to significantly impair the piezoelectricity of this composite film. For example, if the thickness of the amorphous film 12 is 1 / 10 or less of the thickness of the ScAlN film 13, the piezoelectricity of the composite film is not significantly impaired.

[0024] The thickness of the amorphous film 12 is measured using an ellipsometer or a TEM image of a cross section of the amorphous film 12. When a TEM image is used, the average value of measurements at 10 points is the thickness of the amorphous film 12 referred to here.

[0025] The ScAlN film 13 is a piezoelectric film made of ScAlN (that is, scandium-containing aluminum nitride). The ScAlN film 13 is disposed on the amorphous film 12. The ScAlN film 13 is in contact with the surface of the amorphous film 12.

[0026] The Sc concentration of the ScAlN film 13 may be any concentration greater than 0 atomic % and equal to or less than 45 atomic %. The Sc concentration is the ratio of the number of Sc atoms to the total number of Sc atoms and Al atoms, which is 100 atomic %. The atomic % refers to hundreds of atomic percentages. The Sc concentration is measured by RBS. RBS is an abbreviation for Rutherford Backscattering Spectrometry. The Sc concentration shown in this specification is a value measured using the following apparatus under the following measurement conditions. Device name: National Electrostatics Corporation Pelletron 3SDH Measurement conditions RBS measurements Incident ions: 4He++ Incident energy: 2300keV Incident angle: 0deg Scattering angle: 160deg Specimen current: 13nA Beam diameter: 2mmφ In-plane rotation: None Irradiance: 70μC

[0027] Next, a method for manufacturing the piezoelectric film laminate 10 of this embodiment will be described. The method for manufacturing the piezoelectric film laminate 10 includes a step S1 for forming the metal film 11, a step S2 for forming the amorphous film 12, and a step S5 for forming the ScAlN film 13, as shown in FIG.

[0028] First, a metal film 11 forming step S1 is performed. That is, the metal film 11 is formed. The metal film 11 is formed on the substrate 1. In order to form the amorphous film 12 by oxidizing or nitriding the metal film 11, the metal film 11 is formed as a material containing at least one metal element of Mo, Al, and Ti. Mo, Al, and Ti are metal elements used as electrode materials, and can form insulating metal compounds by oxidation or nitridation. The metal film 11 may be formed of an alloy containing two or more metal elements of Mo, Al, and Ti.

[0029] Subsequently, a step S2 of forming an amorphous film 12 is performed. That is, an insulating amorphous film 12 is formed on the metal film 11 so as to be in contact with the surface of the metal film 11. The surface layer of the metal film 11 is oxidized or nitridized to form the amorphous film 12 made of a material containing an oxide or nitride of at least one of the metal elements Mo, Al, and Ti.

[0030] Here, as an example, a case where the amorphous film 12 is made of a material containing Mo oxide will be described. First, in a metal film 11 forming step S1, the metal film 11 made of a material containing Mo is formed on the substrate 1 made of a Si substrate by a sputtering method so as to be in contact with the surface of the substrate 1. In this manner, the metal film 11 is disposed in contact with the surface of a base material made of a material other than AlN. That is, no AlN film exists under the metal film 11. Then, in an amorphous film 12 forming step S2, the surface layer of the metal film 11 is oxidized to form the amorphous film 12 made of a material containing Mo oxide. The oxidation method is carried out by leaving it in the air or by heat treatment.

[0031] In the air exposure method, the metal film 11 is exposed to the air. The exposure time determines the thickness of the amorphous film 12. Therefore, the exposure time is set so that the amorphous film 12 has the above-mentioned thickness.

[0032] FIG. 3 shows the relationship between the time when the metal film 11 mainly composed of Mo is left in the air at room temperature and normal humidity and the thickness of the amorphous film 12. The horizontal axis indicates the time when the film is left in the air. The film thickness shown in FIG. 3 is a value measured using an ellipsometer. As shown in FIG. 3, the thickness of the amorphous film 12 increases as the time when the film is left is increased. By setting the time to about 200 hours, the thickness of the amorphous film 12 can be set to about 10 Å (i.e., 1.0 nm). In FIG. 3, the film thickness is 0 when the time is left for 40 hours or less. This is because the thickness of the amorphous film 12 could not be measured when the time is left for 40 hours or less. In this embodiment, the time when the film is left for more than 40 hours is set. As a result, an amorphous film 12 having a thickness of about 1 Å (i.e., 0.1 nm) or more is obtained.

[0033] In the heat treatment, the metal film 11 is heated in an atmosphere containing oxygen. The heating temperature is preferably 100° C. or higher and 250° C. or lower. By performing heat treatment on the metal film 11, which is mainly composed of Mo, using a quartz tube, under 100% oxygen, atmospheric pressure, a temperature of 200° C., and a time of 1 hour, the thickness of the amorphous film 12 can be set to 6.5 nm.

[0034] In the conventional manufacturing method of a device having a lower electrode, a metal film patterning process is performed after the metal film formation process, in which the metal film is patterned into a predetermined shape by photolithography and etching to form the lower electrode.

[0035] Unlike the present embodiment, a case is assumed in which, after the step S1 of forming the metal film 11, the step S2 of forming the amorphous film 12 is not performed, and the step S5 of forming the ScAlN film 13 is performed. In this case, after the step S1 of forming the metal film 11 and before the step S5 of forming the ScAlN film 13, a patterning step of the metal film 11 is performed in the same manner as the above-mentioned patterning step of the metal film. In this case, the metal film 11 is exposed to the atmosphere during the period from the formation of the metal film 11 to the start of the formation of the ScAlN film 13. Therefore, even if the step S2 of forming the amorphous film 12 is not performed, the surface layer of the metal film 11 naturally oxidizes to some extent.

[0036] However, even in consideration of these steps, for mass production of devices, the time interval between the formation of the metal film 11 and the formation of the ScAlN film 13 is usually about one day at most. If the natural oxidation time is about one day, the thickness of the oxide film formed is too large to be measured, as can be seen from FIG. 3, and does not reach the preferable thickness of the amorphous film 12 described above (i.e., 1.0 nm or more).

[0037] After the step S2 of forming the amorphous film 12, a step S5 of forming the ScAlN film 13 is performed. That is, the ScAlN film 13 is formed on the amorphous film 12 so as to be in contact with the surface of the amorphous film 12. The ScAlN film 13 is formed by reactive sputtering at a predetermined film formation temperature. In this way, the piezoelectric film laminate 10 of this embodiment is manufactured.

[0038] Similarly to the manufacturing method of the conventional device described above, the manufacturing method of the piezoelectric film laminate 10 of this embodiment includes the patterning step S3 of the metal film 11. The forming step S2 of the amorphous film 12 may be performed either before or after the patterning step S3 of the metal film 11.

[0039] However, due to the patterning step S3 of the metal film 11, various contaminants may adhere to the surface of the metal film 11. If the surface layer of the metal film 11 is oxidized in a state in which contaminants are attached, there is a high possibility that the contaminants will diffuse into the metal film 11. In particular, if the surface layer of the metal film 11 is oxidized by thermal oxidation in a state in which contaminants are attached, there is a high possibility that the heating device will be contaminated. For this reason, as shown in FIG. 2, it is preferable that the forming step S2 of the amorphous film 12 is performed before the patterning step S3 of the metal film 11. This makes it possible to avoid the diffusion of contaminants into the metal film and the contamination of the heating device by the contaminants.

[0040] 2, the method for manufacturing the piezoelectric film laminate 10 of this embodiment includes a cleaning step S4. The cleaning step S4 is performed after the step S2 of forming the amorphous film 12 and before the step S5 of forming the ScAlN film 13. In the cleaning step, the surface layer of the amorphous film 12 is removed to remove dirt on the amorphous film 12.

[0041] The cleaning step S4 is performed to improve the crystallinity of ScAlN when the ScAlN film 13 is formed. The cleaning step S4 is performed in the film formation chamber where the ScAlN film 13 is formed, or in a separate chamber to which the film can be transported while maintaining a vacuum. In the cleaning step S4, Ar gas is introduced into the chamber and discharged to generate Ar ions, which are then irradiated onto the surface of the amorphous film 12, thereby sputtering and removing dirt on the amorphous film 12. At this time, not only the dirt but also the surface layer of the amorphous film 12 is removed, so that the thickness of the amorphous film 12 is reduced.

[0042] Therefore, in the forming step S2 of the amorphous film 12, the thickness of the formed amorphous film 12 is set to a thickness obtained by adding the thickness of the surface layer of the amorphous film 12 to be removed in the cleaning step S4 to the target thickness of the amorphous film 12 after the cleaning step S4 is performed. This makes it possible to set the thickness of the amorphous film 12 after the cleaning step S4 within the above-mentioned film thickness range.

[0043] As described above, the piezoelectric film laminate 10 of this embodiment includes the metal film 11, the insulating amorphous film 12, and the ScAlN film 13. The method for manufacturing the piezoelectric film laminate 10 of this embodiment includes a step S1 of forming the metal film 11, a step S2 of forming the amorphous film 12, and a step S5 of forming the ScAlN film 13.

[0044] Here, unlike the present embodiment, when a ScAlN film is formed in contact with the surface of an electrode, the crystallinity of the resulting ScAlN film decreases depending on the material that constitutes the electrode. In particular, when the electrode is made of a material that contains Mo, the crystallinity of the resulting ScAlN film decreases. Also, depending on the magnitude of the residual stress of the ScAlN film, that is, when the residual stress of the ScAlN film is larger than an appropriate magnitude, the crystallinity of the resulting ScAlN film decreases. When the crystallinity of the ScAlN film decreases, the piezoelectricity of the ScAlN film decreases.

[0045] In contrast, according to this embodiment, the ScAlN film 13 is formed in contact with the surface of the amorphous film 12. Therefore, ScAlN can be self-oriented without the influence of the crystal structure of the base. That is, when the base has a crystal structure, the lattice constant of the crystal structure affects the crystal growth of ScAlN. In contrast, according to this embodiment, ScAlN can be crystal-grown without this influence. Therefore, it is possible to form an ScAlN film 13 with higher crystallinity than when the ScAlN film is formed in contact with the surface of a base having a crystal structure. By increasing the crystallinity of the ScAlN film, it is possible to improve the piezoelectricity of the ScAlN film.

[0046] Here, Fig. 4 shows the results of an experiment conducted by the present inventor. Fig. 4 is a graph showing the relationship between the crystallinity of the ScAlN film and the time that the metal film 11 was left standing in the air. The vertical axis of Fig. 4 is the half-width of the rocking curve for the X-ray diffraction peak of the (0002) plane of the ScAlN crystal. The horizontal axis of Fig. 4 is the time that the metal film 11 was left standing in the air to form the amorphous film 12. Sc24%, Sc32%, and Sc38% in Fig. 4 indicate that the Sc concentrations of the ScAlN film 13 are 24 atomic %, 32 atomic %, and 38 atomic %, respectively.

[0047] The inventors manufactured a plurality of piezoelectric film laminates 10 in which the Sc concentration in the ScAlN film 13 was either 24 atomic %, 32 atomic %, or 38 atomic %, and the thickness of the amorphous film 12 was different. In all of the plurality of piezoelectric film laminates 10, the metal film 11 was made of a material containing Mo, and the amorphous film 12 was made of a material containing Mo oxide.

[0048] The inventors formed the metal film 11 on a Si substrate by sputtering. The deposition conditions for the metal film 11 are as follows. Target Type: Mo Target Target size: diameter 100mm Atmosphere type: Ar Pressure: 0.2Pa Substrate temperature: 400℃ DC power: 250W Film thickness: 70nm

[0049] Thereafter, the metal film 11 was left in the air to form an amorphous film 12 on the metal film 11. At this time, the leaving time was set to various times to form amorphous films 12 with different thicknesses.

[0050] Thereafter, the ScAlN film 13 was formed by reactive sputtering on the amorphous film 12. The film formation conditions for the ScAlN film 13 were as follows. Target type: ScAl target Target size: diameter 100mm Distance between Si substrate and target: 200 mm DC Power: 800W Pulse frequency: 20kHz Pulse length: 4μs Gas flow rate: N2: 28sccm, Ar: 28sccm Gas pressure: 0.2Pa Si substrate temperature: 370℃ Resistivity of Si substrate: ≧1×10 3 Ω cm At this time, three ScAl targets with preset Sc concentrations were used so that the ScAlN film 13 after deposition would have Sc concentrations of 24 atomic %, 32 atomic %, and 38 atomic %.

[0051] The smaller the half-width on the vertical axis in FIG. 4, the higher the crystallinity of ScAlN. In FIG. 4, when the Sc concentration of the ScAlN film 13 is 24 atomic %, 32 atomic %, or 38 atomic %, in the range where the exposure time is less than 200 hours, the half-width decreases as the exposure time increases. In the range where the exposure time is 200 hours or more, the ratio of the decrease in the half-width to the increase in the exposure time is smaller than that in the range where the exposure time is less than 200 hours. That is, in the range where the exposure time is 200 hours or more, even if the exposure time increases, the half-width is almost constant at a value close to the minimum value of the half-width at each Sc concentration. That is, in the range where the exposure time is 200 hours or more, the half-width is within a range close to the minimum value. When the exposure time is 200 hours or more, the effect of improving the crystallinity is saturated. From this, it can be seen that in order to improve the crystallinity of ScAlN, it is better to leave it for a long time, and in particular, it is preferable for the exposure time to be 200 hours or more.

[0052] 3, the measured film thickness at two points near the time of leaving for 200 hours is about 10 Å (that is, about 1.0 nm). Therefore, the film thickness of the amorphous film 12 is preferably 1.0 nm or more.

[0053] Note that FIG. 4 shows the results when the Sc concentration of the ScAlN film 13 is 24 atomic % or more and 38 atomic % or less. However, even when the Sc concentration is other than this, it is estimated that the half-width will fall within a range close to the minimum value when the exposure time is 200 hours or more.

[0054] Conventionally, when a metal film containing Mo is used as the underlayer of a ScAlN film, an underlayer made of AlN, called a seed layer, is used under the metal film in order to improve the crystallinity of Mo. That is, in the process of forming the metal film, the metal film is formed in contact with the underlayer made of AlN.

[0055] In contrast, according to this embodiment, the ScAlN film 13 can be formed without being affected by the crystallinity of the metal film 11. That is, the crystallinity of the metal film 11 does not affect the crystallinity of the ScAlN film 13. Therefore, according to this embodiment, there is also an effect that restrictions on the crystallinity of Mo are eliminated.

[0056] Therefore, according to this embodiment, when the metal film 11 is made of a material containing Mo and the amorphous film 12 is made of a material containing Mo oxide, the metal film 11 can be disposed in contact with the surface of the base material 1, which serves as a base and is made of a material other than AlN. In this case, the film formation conditions of the metal film 11 also have a high degree of freedom, and it is possible to ignore the crystallinity of Mo and select film formation conditions specialized for controlling the film stress, for example. Note that even when the metal film 11 is disposed in contact with the surface of another film on the base material 1, the other film serving as a base for the metal film 11 may be made of a material other than AlN.

[0057] Second embodiment In this embodiment, unlike the first embodiment, the amorphous film 12 is formed in the amorphous film 12 formation step S2 by a film formation method. Examples of the film formation method include physical vapor deposition and chemical vapor deposition. When forming the amorphous film 12 by a film formation method, the conditions for forming a film having a crystalline structure are changed to "lower the substrate temperature," "increase the film formation pressure," "increase the input power to increase the film formation speed," and the like. In this way, the amorphous film 12 can be formed.

[0058] In the metal film 11 forming step S1, the metal film 11 is formed from a material containing a metal element used as an electrode material. Examples of the metal element used as an electrode material include Mo, Al, Ti, Ru, Pt, Au, etc. In this embodiment, the metal element contained in the material constituting the amorphous film 12 may be the same as or different from the metal element contained in the material constituting the metal film 11.

[0059] Other configurations of the piezoelectric film laminate 10 and the manufacturing method of the piezoelectric film laminate 10 are the same as those of the first embodiment. According to this embodiment, too, it is possible to obtain the same effects as those of the first embodiment, which are provided by the configuration common to the first embodiment.

[0060] Third embodiment As shown in FIG. 5, a piezoelectric film laminate 10A of this embodiment includes a substrate 1, a conductive amorphous film 14, and a ScAlN film 13. The piezoelectric film laminate 10A includes a substrate 1, a conductive amorphous film 14, and a ScAlN film 13.

[0061] The amorphous film 14 is disposed on the substrate 1. The amorphous film 14 is in contact with the surface of the substrate 1. The ScAlN film 13 is disposed on the amorphous film 14. The ScAlN film 13 is in contact with the surface of the amorphous film 14. The configurations of the substrate 1 and the ScAlN film 13 are the same as those in the first embodiment.

[0062] The amorphous film 14 is a film made of a conductive amorphous material. In this specification, the term "conductive" refers to a film having an electrical resistivity (i.e., volume resistivity) of 10 -2 This means that the resistance is less than Ω m.

[0063] Examples of materials constituting the amorphous film 14 include conductive metal oxides and conductive metal nitrides. Examples of conductive metal oxides include Ru oxide and ITO. ITO is an abbreviation for Indium Tin Oxide.

[0064] The method for manufacturing the piezoelectric film laminate 10A of this embodiment includes a step of forming the amorphous film 14 and a step of forming the ScAlN film 13.

[0065] In the process of forming the amorphous film 14, a metal film (not shown) made of a material containing a metal element capable of forming a conductive metal oxide or a conductive metal nitride is formed. The entire metal film is then oxidized or nitrided to form the amorphous film 14. In this case, the entire metal film becomes the amorphous film 14. The amorphous film 14 may be formed on the metal film by oxidizing or nitriding the surface layer of the metal film.

[0066] Furthermore, without being limited thereto, in the step of forming the amorphous film 14, the amorphous film 14 may be formed by a film formation method. Examples of the film formation method include physical vapor deposition and chemical vapor deposition. When forming the amorphous film 14 by a film formation method, the conditions for forming a film having a crystalline structure are changed to "lower the substrate temperature," "increase the film formation pressure," "increase the input power to increase the film formation speed," and the like. In this way, the amorphous film 14 can be formed.

[0067] Furthermore, when the amorphous film 14 is formed by a film formation method, the amorphous film 14 may be formed on a metal film in contact with the surface of the metal film. For example, the amorphous film 14 may be formed on a metal film made of a material containing Mo in contact with the surface of the metal film. In this case, as described in the first embodiment, the metal film 11 can be disposed in contact with the surface of the base material 1 as a base made of a material other than AlN.

[0068] The process of forming the ScAlN film 13 is the same as in the first embodiment. In this embodiment as well, the same effects as those in the first embodiment can be obtained from the configuration common to the first embodiment.

[0069] (Fourth embodiment) 6, the piezoelectric film laminate 10B of this embodiment includes a substrate 1, a metal film 15, a conductive amorphous film 16, and an ScAlN film 13. In this embodiment, the metal film 15 and the conductive amorphous film 16 are used as a lower electrode in a device.

[0070] The structure of the substrate 1 is the same as that of the first embodiment. The metal film 15 is a film made of a metal material. The metal film 15 is disposed on the substrate 1. The metal film 15 is in contact with the surface of the substrate 1.

[0071] The amorphous film 16 is disposed on the metal film 15. The amorphous film 16 is in contact with the surface of the metal film 15. The amorphous film 16 is formed by subjecting the surface layer of the metal film 15 to ion implantation or plasma treatment as described below.

[0072] 7, the method for manufacturing the piezoelectric film laminate 10B of this embodiment includes a step S11 of forming a metal film 15, a step S12 of forming an amorphous film 16, and a step S13 of forming an ScAlN film 13. In the step S11 of forming the metal film 15, the metal film 15 that serves as a base for forming the amorphous film 16 is formed on the base material 1. In the step S12 of forming the amorphous film 16, the metal film 15 is subjected to ion implantation or plasma treatment to form the amorphous film 16.

[0073] In the ion implantation into the metal film 15, metal ions, rare gas ions, etc. are used as the ion implantation species. By applying energy of about several tens to 100 keV to the surface layer of the metal film 15, it is possible to form an amorphous film 16 having a thickness of about several tens to 100 nm. By using metal ions, rare gas ions, etc. as the ion implantation species, it is possible to maintain the conductivity of the metal to be ion implanted.

[0074] The plasma treatment of the metal film 15 can be performed by the method described in the following document. That is, a chamber configuration generally used for dry etching (i.e., a layout in which a substrate and a counter electrode are arranged in parallel) is used. In this chamber configuration, plasma is generated by high-frequency discharge, as in a normal dry etching process. At this time, by introducing only Ar gas as the material gas, etching of the metal film 15 can be minimized and the surface layer of the metal film 15 can be made amorphous. Impact of the surface-near silicon substrate properties on the microstructure of sputter-deposited AlN thin filmsAuthors: Schneider, M.; Bittner, A.; Patocka, F.; et al.APPLIED PHYSICS LETTERS Volume: 101 Issue: 22 Article Number: 221602 Publication: NOV 26 2012

[0075] The process of forming the ScAlN film 13 is the same as in the first embodiment. This embodiment also provides the same effects as the first embodiment, which are achieved by the configuration common to the first embodiment. In this embodiment, when the metal film 15 is made of a material containing Mo, the metal film 15 can be disposed in contact with the surface of the base material 1 as a base made of a material other than AlN. In this case, the amorphous film 16 is made of a material containing Mo.

[0076] Fifth embodiment 8 uses the piezoelectric film laminate 10 of the first embodiment. The microphone 20 includes a pressure receiving portion 21 and a support 22. The pressure receiving portion 21 is a membrane-like portion that receives sound pressure. The support 22 supports the pressure receiving portion 21.

[0077] The support 22 has a space 23 for the pressure-receiving portion 21 to deform when subjected to sound pressure. The support 22 supports the pressure-receiving portion 21 with the pressure-receiving portion 21 positioned above the space 23 so that the pressure-receiving portion 21 can deform when subjected to sound pressure. The support 22 is made of Si.

[0078] The pressure-receiving portion 21 includes a piezoelectric film 24, a lower electrode 25, an upper electrode 26, and an insulating film 27. The ScAlN film 13 of the first embodiment is used as the piezoelectric film 24. The metal film 11 and the amorphous film 12 of the first embodiment are used as the lower electrode 25. The upper electrode 26 is formed in contact with the upper surface of the piezoelectric film 24. The lower electrode 25 and the upper electrode 26 are electrodes for recovering charges generated in the piezoelectric film 24 due to deformation of the pressure-receiving portion 21. The insulating film 27 covers the space 23 and the area surrounding the space 23 of the support 22. The insulating film 27 is a Si oxide film.

[0079] The lower electrode 25 is provided on the surface of a region of the insulating film 27 located above the space 23. The piezoelectric film 24 is formed over the upper surface of the lower electrode 25 and the surface of the insulating film 27 on which the lower electrode 25 is not formed.

[0080] In the microphone 20 configured in this manner, the pressure receiving portion 21 is deflected and deformed when subjected to sound pressure. When the pressure receiving portion 21 is deformed into a downward convex shape, a compressive stress is generated in the in-plane direction of the piezoelectric film 24. At this time, charges are generated on the surface of the piezoelectric film 24 due to the piezoelectric effect. Also, when the pressure receiving portion 21 is deformed into an upward convex shape, a tensile stress is generated in the in-plane direction of the piezoelectric film 24. At this time, charges of the opposite polarity to when compressive stress is generated are generated on the surface of the piezoelectric film 24 due to the piezoelectric effect. Therefore, by collecting the generated charges through the lower electrode 25 and the upper electrode 26, the sound pressure applied to the pressure receiving portion 21 can be detected.

[0081] According to this embodiment, the ScAlN film 13 of the first embodiment is used as the piezoelectric film 24. As described in the first embodiment, the ScAlN film 13 has high crystallinity of ScAlN and therefore has high piezoelectricity. Therefore, the sensitivity of the microphone 20 can be improved.

[0082] In this embodiment, the insulating film 27 is included in the pressure receiving portion 21. However, the insulating film 27 may be a conductive film separate from the lower electrode 25. In this embodiment, the insulating film 27 is formed so that the neutral line in the bending deformation of the pressure receiving portion 21 does not exist in the piezoelectric film 24. When the neutral line in the bending deformation of the pressure receiving portion 21 does not exist in the piezoelectric film 24 by making the lower electrode 25 thicker than the upper electrode 26, for example, the insulating film 27 may not be included in the pressure receiving portion 21. In this embodiment, the piezoelectric film 24, the lower electrode 25, and the upper electrode 26 have shapes shown in FIG. 8. However, these shapes are not limited to the shapes shown in FIG. 8.

[0083] Furthermore, the microphone 20 of this embodiment uses the piezoelectric film laminate 10 of the first embodiment. However, the piezoelectric film laminate 10A of the third embodiment may be used. In this case, the conductive amorphous film 14 is used alone as the lower electrode 25. Alternatively, the conductive amorphous film 14 and a metal film in contact with the lower surface of the amorphous film 14 are used as the lower electrode 25. Similarly, the microphone 20 of this embodiment may use the piezoelectric film laminate 10B of the fourth embodiment. In this case, the metal film 15 and the conductive amorphous film 16 are used as the lower electrode 25.

[0084] Sixth embodiment 9 is a BAW device using the piezoelectric film laminate 10 of the first embodiment. BAW is an abbreviation for Bulk Acoustic Wave. The BAW resonator 30 includes a piezoelectric film 31, a lower electrode 32, an upper electrode 33, and a support 34.

[0085] The ScAlN film 13 of the first embodiment is used as the piezoelectric film 31. The metal film 11 and the amorphous film 12 of the first embodiment are used as the lower electrode 32. The upper electrode 33 is formed in contact with the upper surface of the piezoelectric film 31. The lower electrode 32 and the upper electrode 33 are electrodes that apply an AC electric field to the piezoelectric film 31 to vibrate the piezoelectric film 31 in the film thickness direction.

[0086] The support 34 supports the piezoelectric film 31, the lower electrode 32, and the upper electrode 33. The support 34 has a space 35 for the piezoelectric film 31 to vibrate when an AC electric field is applied to the piezoelectric film 31. The support 34 is made of Si. The lower electrode 32 faces the space 35 of the support 34. In this embodiment, the piezoelectric film 31 is formed on the surface of the lower electrode 32 and on the surface of the support 34.

[0087] In the BAW resonator 30 configured in this manner, when a voltage is applied between the upper electrode 33 and the lower electrode 32, the piezoelectric film 31 expands and contracts in the film thickness direction shown by the arrow in FIG. 9 due to the inverse piezoelectric effect. When a sinusoidal voltage waveform is applied, this expansion and contraction vibration also has a sinusoidal vibration waveform. When this frequency coincides with the resonant frequency of the mechanical vibration, the impedance between the upper electrode 33 and the lower electrode 32 changes significantly. This makes the BAW resonator 30 of this embodiment an electrical resonator. By using a plurality of such resonators and connecting them in a circuit, a filter operation is possible.

[0088] According to this embodiment, the ScAlN film 13 of the first embodiment is used as the piezoelectric film 31. As described in the first embodiment, the ScAlN film 13 has high piezoelectricity due to the high crystallinity of ScAlN. This allows the filter band to be widened.

[0089] In the BAW resonator 30 of this embodiment, the support 34 has the space 35. However, the support 34 does not have to have the space 35. In this case, the BAW resonator 30 only needs to include an acoustic multilayer film between the lower electrode 32 and the support 34.

[0090] In addition, the BAW resonator 30 of this embodiment uses the piezoelectric film laminate 10 of the first embodiment. However, the piezoelectric film laminate 10A of the third embodiment may be used. In this case, the conductive amorphous film 14 is used alone as the lower electrode 32. Alternatively, the conductive amorphous film 14 and a metal film in contact with the lower surface of the amorphous film 14 are used as the lower electrode 32. Similarly, the piezoelectric film laminate 10B of the fourth embodiment may be used in the BAW resonator 30 of this embodiment. In this case, the metal film 15 and the conductive amorphous film 16 are used as the lower electrode 32.

[0091] Seventh embodiment 10, a SAW device 40 of this embodiment uses the piezoelectric film laminate 10 of the first embodiment. SAW is an abbreviation for Surface Acoustic Wave.

[0092] The SAW device 40 includes a substrate 41, a piezoelectric film 42, and a comb-tooth electrode 43. The substrate 41 is made of Si. The piezoelectric film laminate 10 of the first embodiment is used as the piezoelectric film 42. The piezoelectric film 42 is provided on the surface of the substrate 41. The comb-tooth electrode 43 is provided on the surface of the piezoelectric film 42. The comb-tooth electrode 43 excites a SAW in the piezoelectric film 42, or receives a SAW propagating through the piezoelectric film 42. The comb-tooth electrode 43 is made of Mo. The SAW device 40 includes a SAW resonator, a SAW filter, and the like.

[0093] Although not shown, an example of a SAW resonator is a one-port SAW resonator. In this SAW resonator, reflectors are arranged on both sides of the comb-tooth electrode 43 on the surface of the piezoelectric film 42. In this SAW resonator, a SAW excited by the comb-tooth electrode 43 is reflected by both reflectors, generating a standing wave. This realizes a resonator.

[0094] Although not shown, another example of a SAW device is a transversal SAW filter. In this SAW filter, the comb-tooth electrode 43 includes an input electrode and an output electrode. The SAW excited by the input electrode propagates along the surface of the piezoelectric film 42 and is detected by the output electrode. This makes it possible to extract an electrical signal in a specific frequency band. According to this embodiment, the piezoelectric film laminate 10 of the first embodiment is used as the piezoelectric film 42. The ScAlN film 13 of the piezoelectric film laminate 10 has high piezoelectricity because ScAlN has high crystallinity. This makes it possible to widen the band of the filter.

[0095] Each of the substrate 41 and the comb-tooth electrode 43 may be made of a material other than the above-mentioned materials. Furthermore, the piezoelectric film 42 may be the piezoelectric film laminate 10A of the third embodiment or the piezoelectric film laminate 10B of the fourth embodiment.

[0096] Eighth embodiment 11 uses the piezoelectric film laminate 10 of the first embodiment. MEMS is an abbreviation for Micro Electro Mechanical Systems.

[0097] The MEMS resonator 50 includes a three-layer structure 51 and a support 52. The three-layer structure 51 includes a piezoelectric film 53, a lower electrode 54, and an upper electrode 55.

[0098] The ScAlN film 13 of the first embodiment is used as the piezoelectric film 53. The metal film 11 and the amorphous film 12 of the first embodiment are used as the lower electrode 54. The upper electrode 55 is formed in contact with the upper surface of the piezoelectric film 53. The lower electrode 54 and the upper electrode 55 are electrodes that apply an AC electric field to the piezoelectric film 53 to expand and contract the piezoelectric film 53 in the in-plane direction of the piezoelectric film 53.

[0099] The support 52 has a space 56. The support 52 supports the three-layer structure 51 in a state in which the three-layer structure 51 can vibrate above the space 56. In this embodiment, a cantilever structure is formed in which one end of the three-layer structure 51 in one direction is fixed to the support 52 and the other end of the three-layer structure 51 in one direction is free. The support 52 includes a substrate 57 and an insulating film 58. The substrate 57 is made of Si. The insulating film 58 is formed on the surface of the substrate 57. The insulating film 58 is a Si oxide film. The lower electrode 54 is formed on the surface of the insulating film 58.

[0100] The thickness of the lower electrode 54 is equal to or greater than the total thickness of the upper electrode 55 and the piezoelectric film 53. Therefore, the neutral line in the flexural deformation of the three-layer structure 51 is inside the lower electrode 54. When a voltage is applied between the upper electrode 55 and the lower electrode 54, the piezoelectric film 53 expands and contracts in the in-plane direction of the film due to the inverse piezoelectric effect. Then, the entire three-layer structure 51 flexes. When a sinusoidal voltage waveform is applied, this flexural deformation also becomes a sinusoidal vibration. When the frequency coincides with the resonant frequency of the flexural vibration, the impedance between the upper electrode 55 and the lower electrode 54 changes significantly. This makes it an electrical resonator. Using this resonator, a reference frequency required for the operation of an arithmetic circuit or the like can be generated.

[0101] According to this embodiment, the ScAlN film 13 of the first embodiment is used as the piezoelectric film 53. As described in the first embodiment, the ScAlN film 13 has high piezoelectricity due to the high crystallinity of ScAlN. Therefore, the characteristics can be improved.

[0102] If the substrate 57 is an insulator, the insulating film 58 may not be formed. In the MEMS resonator 50 of this embodiment, the piezoelectric film laminate 10 of the first embodiment is used. However, the piezoelectric film laminate 10A of the third embodiment may be used. In this case, the conductive amorphous film 14 is used alone as the lower electrode 54. Alternatively, the conductive amorphous film 14 and a metal film in contact with the lower surface of the amorphous film 14 are used as the lower electrode 54. Similarly, the piezoelectric film laminate 10B of the fourth embodiment may be used in the MEMS resonator 50 of this embodiment. In this case, the metal film 15 and the conductive amorphous film 16 are used as the lower electrode 54.

[0103] (Other embodiments) (1) The piezoelectric film laminates 10, 10A, and 10B of the first to fourth embodiments include an ScAlN film 13. However, even if the piezoelectric film laminates 10, 10A, and 10B include a film made of a wurtzite-based material such as AlN or ZnO instead of the ScAlN film 13, the same effects as those of the first embodiment may be obtained.

[0104] (2) The present invention is not limited to the above-described embodiment, and can be appropriately modified within the scope of the claims, and includes various modified examples and modifications within the equivalent scope. The above-described embodiments are not unrelated to each other, and can be appropriately combined, except when the combination is clearly impossible. In the above-described embodiments, it goes without saying that the elements constituting the embodiments are not necessarily essential, except when they are specifically stated to be essential or when they are clearly considered to be essential in principle. In the above-described embodiments, when the numbers, values, amounts, ranges, etc. of the components of the embodiments are mentioned, they are not limited to the specific numbers, except when they are specifically stated to be essential or when they are clearly limited to a specific number in principle. In the above-described embodiments, when the materials, shapes, positional relationships, etc. of the components are mentioned, they are not limited to the materials, shapes, positional relationships, etc., except when they are specifically stated to be essential or when they are clearly limited to a specific material, shape, positional relationship, etc. in principle. [Explanation of symbols]

[0105] 10 Piezoelectric film laminate 11 Metal Film 12 Insulating amorphous film 13 ScAlN membrane

Claims

1. A piezoelectric film laminate, A metal film (11); an insulating amorphous film (12) disposed on the metal film; a ScAlN film (13) disposed on the amorphous film and in contact with a surface of the amorphous film; A piezoelectric film laminate, wherein the amorphous film has a thickness of 1.0 nm or more and is 1 / 10 or less of the thickness of the ScAlN film.

2. The piezoelectric film laminate according to claim 1 , wherein the amorphous film is made of a material containing Mo oxide.

3. The piezoelectric film laminate according to claim 2 , wherein the metal film is made of a material containing Mo.

4. 4. The piezoelectric film laminate according to claim 3, wherein the metal film is disposed in contact with a surface of a base (1) made of a material other than AlN.

5. A piezoelectric film laminate, A conductive amorphous film (14, 16); a ScAlN film (13) disposed on the amorphous film and in contact with a surface of the amorphous film,

6. The amorphous film (16) is disposed on a metal film (15) made of a material containing Mo; 6. The piezoelectric film laminate according to claim 5, wherein the metal film is disposed in contact with a surface of a base (1) made of a material other than AlN.

7. A piezoelectric film laminate as described in any one of claims 1 to 4 and 6, comprising an upper electrode (26) on the upper surface of the ScAlN film, and the total thickness of the metal film and the amorphous film is thicker than that of the upper electrode.

8. A piezoelectric film laminate as described in claim 5 or 6, wherein the amorphous film is composed of a material containing at least Ru oxide or indium tin oxide.

9. 9. The piezoelectric film laminate according to claim 1, wherein the Sc concentration in said ScAlN film is in the range of 24 atomic % to 38 atomic % relative to a total amount of 100 atomic % of Sc atoms and Al atoms.

10. A method for manufacturing a piezoelectric film laminate, comprising the steps of: forming a metal film (11); forming an insulating amorphous film (12) on the metal film; forming a ScAlN film (13) on the amorphous film so as to be in contact with a surface of the amorphous film; A method for manufacturing a piezoelectric film laminate, in which the amorphous film is formed by oxidizing or nitriding a surface layer of the metal film, thereby forming the amorphous film with a thickness of 1.0 nm or more and 1 / 10 or less of the thickness of the ScAlN film.

11. The method for producing a piezoelectric film laminate according to claim 10, wherein in forming the metal film, a metal film made of a material containing at least one metal element selected from the group consisting of Mo, Al, and Ti is formed.

12. In forming the metal film, a metal film made of a material containing Mo is formed as the metal film, The method for producing a piezoelectric film laminate according to claim 10, wherein in forming the amorphous film, a surface layer of the metal film is oxidized to form an amorphous film made of a material containing Mo oxide.

13. The method for manufacturing the piezoelectric film laminate includes forming the metal film and then patterning the metal film, 13. The method for manufacturing a piezoelectric film laminate according to claim 10, wherein the amorphous film is formed before the metal film is patterned.

14. The method for manufacturing the piezoelectric film laminate includes, after forming the amorphous film and before forming the ScAlN film, removing a surface layer of the amorphous film to remove dirt on the amorphous film; 14. A method for manufacturing a piezoelectric film laminate according to claim 10, wherein, in forming the amorphous film, a thickness of the amorphous film after formation is set to a thickness obtained by adding a thickness of a surface layer of the amorphous film to be removed in removing the dirt to a target thickness of the amorphous film after removing the dirt.

15. providing a top electrode (26) on the top surface of the ScAlN film; 15. The method for producing a piezoelectric film laminate according to claim 10, wherein a total thickness of said metal film and said amorphous film is made thicker than that of said upper electrode.

16. 16. The method for manufacturing a piezoelectric film laminate according to claim 10, wherein the Sc concentration in the ScAlN film is in the range of 24 atomic % to 38 atomic % relative to a total amount of 100 atomic % of Sc atoms and Al atoms.

17. A method for manufacturing a piezoelectric film laminate, comprising the steps of: forming a conductive amorphous film (16); forming a ScAlN film (13) on the amorphous film so as to be in contact with a surface of the amorphous film; In the method for producing a piezoelectric film laminate, the amorphous film is formed by subjecting a metal film (15) to ion implantation or plasma treatment.

Citation Information

Patent Citations

  • Method for reactive sputter deposition of an ultra-thin metal oxide film

    CN1740376A

  • Hitensosasochi

    JP1976090841A

  • Manufacture of semiconductor device

    JP1983182873A

  • Flattened tunnel magnetoresistance element

    JP2003318465A

  • Piezoelectric thin film, piezoelectric material, fabrication method of piezoelectric thin film and piezoelectric material, and piezoelectric resonator, actuator element and physical sensor using piezoelectric thin film

    JP2009010926A